Supply and demand: Will we have enough vascular surgeons by 2030?. (August 2016) - Williams, Katherine; Schneider, Brandon; Lajos, Paul; Marin, Michael; Faries, Peter
The increase in prevalence of certain cardiovascular risk factors increases susceptibility to vascular disease, which may create demand for surgical intervention. In our study, data collected by the American Association of Medical Colleges Physician Specialty Databook of 2012, the United States Census Bureau, and other nationwide organizations were referenced to calculate future changes in vascular surgeon supply and prevalence of people at risk for vascular disease. In 2010, there were 2853 active vascular surgeons. By 2040, the workforce is expected to linearly rise to 3573. There will be an exponential rise in people with cardiovascular risk factors. Adding to concern, in 2030, an estimated 3333 vascular surgeons will be available for 180, 000, 000 people with at least one risk factor for peripheral arterial disease. The paucity of properly trained surgeons entering the workforce needs to be addressed before this shortage becomes a larger burden on healthcare providers and governmental spending.